Climate and soil properties regulate soil fungal communities on the Loess Plateau - Zeng, Quanchao; Liu, Yang; Xiao, Li; An, Shaoshan (Pedobiologia, 2020)
•Soil fungal communities were studied in three vegetation types on the Loess Plateau along a latitudinal gradient.•Desert soil had lower fungal diversity than grassland and forest soils.•Basidiomycota were the most abundant in forests, whereas Ascomycota were the most abundant in deserts.•Precipitation was the key variable associated with fungal community distributions on the Loess Plateau. This study investigated the effects of environmental variables on soil fungal communities under different vegetation types in order to advance our understanding of soil fungal community assembly associated with restored vegetation and under different climate conditions. Three vegetation types (no grazing and logging in grasslands and forests, and planted herbs and small shrubs in bare land in the desert) on the Loess Plateau in China were chosen as subjects, and pyrosequencing of the 18S rRNA gene region was used to analyze the changes in the diversity and community composition of soil fungi. Vegetation type had significant effects on soil fungal diversity. The forest and grassland soils had similar fungal diversity levels, which were significantly higher than that of the desert ecosystem. Multiple regression models indicated that total phosphorus in soil and the ratio of soil organic carbon to total nitrogen in soil (C:N) were the best predictors of soil fungal diversity. Ascomycota and Basidiomycota were the most dominant phyla in all soils, accounting for 83.6 % of fungal sequences. Dothideomycetes (26.6 %), Sordariomycetes (18.3 %), Eurotiomycetes (8.5 %), Pezizomycetes (12.1 %) and Dothideomycetes (10.7 %) were the dominant classes across the three vegetation types. Agaricomycetes and Sordariomycetes were more dominant in forest soils than grasslands and desert soils, while Pezizomycetes were more frequently observed in desert soils. Along an increasing mean annual precipitation (MAP) gradient, relative abundance of the Ascomycota phylum decreased and that of the Basidiomycota increased. Among local environmental factors, MAP, soil pH and soil organic matter were the main factors influencing the soil fungal community composition, explaining 20.9 %, 15.9 % and 10.4 % of the variation in the fungal community, respectively. Considering geographic distance, variation partitioning revealed that geographic distance explained more of the fungal community variation than measured environmental factors. This finding may help to predict the consequences in fungal communities in response to climate change and vegetation restoration in arid areas.